Competence and Motivation to The Performance of Baznaz Officers through Work Discipline - Abadi, Hamdi; Ansar; Farida, Umi (Journal of Indonesian Scholars for Social Research, 2024)
This study aims to analyze the effect of competence on the performance of BAZNAS officers. This research uses a quantitative approach. The population of this study was UPZ Baznaz officers, with a total of 194 employees. Data collection techniques used observation, interviews, documentation, and questionnaires. The analysis method used is path analysis using the SPSS 26 program. The results of this study indicate that 1) Competence affects work discipline in Baznaz Officers of Bone Regency; 2) Motivation affects work discipline in Bone Regency Baznaz Officers; 3) Competence affects the performance of Bone Regency Baznaz Officers; 4) Motivation affects performance in Bone Regency Baznaz Officers; 5) Work discipline affects performance in Bone Regency Baznaz Officers; 6) Competence affects officer performance through work discipline in Bone Regency Baznaz Officers; 7) Motivation affects officer performance through work discipline in Bone Regency Baznaz Officers.